Integrated Management of Chronic Diseases: Combining Modern Medicine with Complementary and Alternative Medicine - Gupta, Rajeev (British Journal of Healthcare and Medical Research, 2024)
Chronic diseases represent a significant burden on healthcare systems worldwide. Traditional modern medicine approaches may not provide comprehensive solutions to manage these conditions effectively. This review aims to explore the integration of modern medicine with complementary and alternative medicine (CAM) in managing chronic diseases, including the evidence supporting the effectiveness of various CAM modalities, challenges associated with integration, and potential benefits to patients. A systematic search of the literature was conducted to identify studies evaluating the combined approach. This review highlights the importance of an integrated healthcare model for the management of chronic diseases, emphasizing the need for further research and collaboration between conventional and CAM practitioners.